From In-Person to Virtual Class, a Model for Using Online Training in the Time of Covid-19 - Silva-Quiroz, J (EDITORA UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2020)
Academic virtual training is slowly gaining ground in Higher Education, but the arrival of Covid-19 has accelerated this process. Undoubtedly, current times are a great opportunity to innovate and bring virtual training closer to educational communities, but it is necessary to do it properly, otherwise, the outcome can be unexpected and, in the critical view of students, it would invalidate this training modality. This article presents a model of how to face virtual training in times of crisis, how to move from a presencial classroom to a virtual one, integrating the potential that digital technologies provide us to generate environments that promote quality learning in students.